Reproductive biology of the soldierbream, Argyrops filamentosus (Valenciennes, 1830) from the Arabian Sea coast of Oman - Jayabalan, N.; AL-Marzouqi, A.; AL-Nahdi, A. (Indian Journal of Fisheries, 2011)
The reproductive biology of the soldierbream, Argyrops filamentosus (Valenciennes, 1830), was studied from the Arabian Sea coast of Oman between April 2005 and March 2007. The females matured (Lm) at an average length of 22.2 cm TL, males matured at a higher length of 27.5 cm TL and both the sexes attained maturity during second year. The occurrence of spent gonads indicated that the spawning in A. filamentosus was between August and March; however, peak spawning was during September–January as evidenced by the incidence of higher percentages of mature females during these months. Higher GSI values of males and females between September and January coincided with the peak spawning season of the fish. While, higher HSI values during July-October showed better nutritional status prior to and during initial spawning months, the fluctuations in the monthly Kn values were not indicative of spawning season. Individual fish appeared to spawn more than once a year. The fecundity of female fish ranged from 73,363 to 386,521 eggs. The annual sex-ratio indicated the dominance of females over males. While, the male to female ratio for 2005-06 differed significantly (x2 = 6.32), the sex-ratio for 2006-07 did not differ significantly (x2 = 1.34). Based on the estimate of Lm, it is recommended that the legal size of the fish for capture needs to be fixed at 30 cm TL in Oman.